Predictors of self-perceived burden among patients with cancer in Hebei, China - Liu, Bing Yang; Sun, Chao; Zhang, Qiu Xia; Lim, Poh Ying; Lee, Khuan (Springer Science and Business Media Deutschland GmbH, 2025)
Introduction: Cancer is the leading cause of death worldwide. Both new cancer cases and deaths are rising annually. The high cost of cancer treatment and the guilt of being dependent on family members for a long time lead to patients with cancer's self-perceived burden (SPB). Previous studies have shown that different countries, populations, and cancer stages have different SPB levels. SPB is a psychological stressor, the high SPB may affect the medical treatment process and decision-making of patients with cancer, which may cause patients to refuse treatment and seriously cause suicidal ideation. Objective: This study aimed to determine the level of SPB and its predictors among patients with cancer in the Fourth Hospital of Hebei Medical University, China. Methods: A cross-sectional study of 977 patients with cancer was recruited by simple random sampling. A self-administered questionnaire was used. Multiple linear regression was used to investigate the predictors of SPB. Results: A total of 566 respondents participated in the study, with a response rate of 58.4%. A total of 88.0% had moderate to severe SPB. The mean ± standard deviation of SPB was 67.75 ± 15.69. The predictors of SPB were parents as caregivers, siblings as caregivers, occupational status before illness, duration of cancer, impact of cancer on the patient’s mobility, treatment of cancer (radiation and chemotherapy), type of cancer, stage of cancer, and coping strategies (confrontation, resignation, and fantasy). Conclusion: The prevalence of SPB is considered high, therefore, healthcare professionals should pay high attention to reducing the SPB of patients with cancer in clinical nursing work. It is recommended that effective intervention measures be implemented to lower the suicide rate among patients with cancer ultimately.